Planktonic Aggregates as Hotspots for Heterotrophic Diazotrophy: The Plot Thickens - Riemann, Lasse; Rahav, Eyal; Passow, Uta; Grossart, Hans-Peter; de Beer, Dirk; Klawonn, Isabell; Eichner, Meri; Benavides, Mar; Bar-Zeev, Edo (Frontiers in Microbiology, 2022)
Biological dinitrogen (N2) fixation is performed solely by specialized bacteria and archaea termed diazotrophs, introducing new reactive nitrogen into aquatic environments. Conventionally, phototrophic cyanobacteria are considered the major diazotrophs in aquatic environments. However, accumulating evidence indicates that diverse non-cyanobacterial diazotrophs (NCDs) inhabit a wide range of aquatic ecosystems, including temperate and polar latitudes, coastal environments and the deep ocean. NCDs are thus suspected to impact global nitrogen cycling decisively, yet their ecological and quantitative importance remain unknown. Here we review recent molecular and biogeochemical evidence demonstrating that pelagic NCDs inhabit and thrive especially on aggregates in diverse aquatic ecosystems. Aggregates are characterized by reduced-oxygen microzones, high C:N ratio (above Redfield) and high availability of labile carbon as compared to the ambient water. We argue that planktonic aggregates are important loci for energetically-expensive N2 fixation by NCDs and propose a conceptual framework for aggregate-associated N2 fixation. Future studies on aggregate-associated diazotrophy, using novel methodological approaches, are encouraged to address the ecological relevance of NCDs for nitrogen cycling in aquatic environments.